Park 7: A Novel Therapeutic Target for Macrophages in Sepsis-Induced Immunosuppression - Cheng, Yanwei; Marion, Tony N.; Cao, Xue; Wang, Wanting; Cao, Yu (Frontiers in Immunology, 2018)
Sepsis remains a serious and life-threatening condition with high morbidity and mortality due to uncontrolled inflammation together with immunosuppression with few therapeutic options. Macrophages are recognized to play essential roles throughout all phases of sepsis and affect both immune homeostasis and inflammatory processes, and macrophage dysfunction is considered to be one of the major causes for sepsis-induced immunosuppression. Currently, Parkinson disease protein 7 (Park 7) is known to play an important role in regulating the production of reactive oxygen species (ROS) through interaction with p47phox, a subunit of NADPH oxidase. ROS are key mediators in initiating toll-like receptor (TLR) signaling pathways to activate macrophages. Emerging evidence has strongly implicated Park 7 as an antagonist for sepsis-induced immunosuppression, which suggests that Park 7 may be a novel therapeutic target for reversing immunosuppression compromised by sepsis. Here, we review the main characteristics of sepsis-induced immunosuppression caused by macrophages and provide a detailed mechanism for how Park 7 antagonizes sepsis-induced immunosuppression initiated by the macrophage inflammatory response. Finally, we further discuss the most promising approach to develop innovative drugs that target Park 7 in patients whose initial presentation is at the late stage of sepsis.